2022
DOI: 10.1002/acr.24647
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Shoe‐Stiffening Inserts on Lower Extremity Kinematics in Individuals With First Metatarsophalangeal Joint Osteoarthritis

Abstract: This article has been accepted for publication and undergone full peer review but has not been through the copyediting, typesetting, pagination and proofreading process, which may lead to differences between this version and the Version of Record. Please cite this article as

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 36 publications
1
3
0
Order By: Relevance
“…Specifically, the ROM decreased by 26.6%. This change was consistent with previous reports in other sports [13,40,41] and was confirmed by SPM analysis. However, the change in the MTP joint during AJRS was greater than that in running, which might be attributed to the mechanics of AJRS, wherein AJRS required propulsion through the forefoot [27].…”
Section: Discussionsupporting
confidence: 93%
“…Specifically, the ROM decreased by 26.6%. This change was consistent with previous reports in other sports [13,40,41] and was confirmed by SPM analysis. However, the change in the MTP joint during AJRS was greater than that in running, which might be attributed to the mechanics of AJRS, wherein AJRS required propulsion through the forefoot [27].…”
Section: Discussionsupporting
confidence: 93%
“…The prevalence of neuropathic pain observed in this study is similar to previous reports in individuals with knee and hip OA. A systematic review and meta-analysis of 39 studies (36 involving the knee and 3 involving the hip) showed a pooled prevalence estimate of 40% (95% confidence interval [95% CI] 32-48) in knee OA and 29% (95% CI [22][23][24][25][26][27][28][29][30][31][32][33][34][35][36][37] in hip OA, using the same case definition of possible/likely neuropathic pain from the PD-Q (6). The prevalence of reporting individual neuropathic symptoms was also high in our study, with 70% reporting ≥1 neuropathic † For short Form 12 (SF-12) scores, scores ranged from 0 to 100, with higher scores indicating better function.…”
Section: Discussionmentioning
confidence: 99%
“…Foot OA most commonly affects the first metatarsophalangeal (MTP) joint and is characterized by the formation of a dorsal exostosis ( 19 ), limited range of motion ( 20 ), and altered walking patterns ( 21 ). Interventions such as footwear and orthoses have been shown to alter the biomechanical function of the foot in individuals with first MTP joint OA ( 22 , 23 ) but show only modest reductions in pain ( 24 , 25 ), suggesting that non‐mechanical factors may contribute to symptoms.…”
Section: Introductionmentioning
confidence: 99%
“…For forefoot joint disorders such as plantar plate tears or hallux rigidus, the use of a thin carbon foot plate (eg, Morton extension) can offset the extension forces during gait, facilitating healing and pain control while maintaining desired activity levels. 32 Meanwhile, heel lifts or gel cups to cushion the calcaneus are prevalent for the management of plantar fasciitis and Achilles disorders, despite limited evidence (Figure 1D). 4,33…”
Section: Orthosis Management For Common Pathologiesmentioning
confidence: 99%